2008
DOI: 10.1093/icesjms/fsn058
|View full text |Cite
|
Sign up to set email alerts
|

The Northwest Atlantic deep-sea red crab (Chaceon quinquedens) population before and after the onset of harvesting

Abstract: Wahle, R. A., Bergeron, C. E., Chute, A. S., Jacobson, L. D., and Chen, Y. 2008. The Northwest Atlantic deep-sea red crab (Chaceon quinquedens) population before and after the onset of harvesting. – ICES Journal of Marine Science, 65: 862–872. The population structure of deep-sea red crab (Chaceon quinquedens) in a nearly unexploited state is compared with its condition three decades later after more than a decade of sustained harvesting. Our study is based on a camera and net trawl survey conducted in 1974, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 25 publications
3
23
3
Order By: Relevance
“…Delgado & Defeo (2004) suggested that, due to the selective exploitation of males, the sperm supply might have become a limiting resource for the population. A similar concern was raised by Wahle et al (2008) for the northwest Atlantic red crab C. quinquedens fishery, where the abundance of large males declined by 42% after three decades of selective harvesting. Our results could support the Delgado & Defeo (2004) hypothesis, considering that most C. notialis males caught in Brazil (supposedly in much lower numbers than in the original population structure) have shown signs of reproductive activity (copula marks), but a proportionally smaller portion of the females seem to have been effectively fertilized.…”
Section: Discussionmentioning
confidence: 77%
“…Delgado & Defeo (2004) suggested that, due to the selective exploitation of males, the sperm supply might have become a limiting resource for the population. A similar concern was raised by Wahle et al (2008) for the northwest Atlantic red crab C. quinquedens fishery, where the abundance of large males declined by 42% after three decades of selective harvesting. Our results could support the Delgado & Defeo (2004) hypothesis, considering that most C. notialis males caught in Brazil (supposedly in much lower numbers than in the original population structure) have shown signs of reproductive activity (copula marks), but a proportionally smaller portion of the females seem to have been effectively fertilized.…”
Section: Discussionmentioning
confidence: 77%
“…Density of crab was calculated as the catch (total number) of each sex divided by the area towed and expressed as the mean number of crab·per hectare, for comparison with results reported by Wahle et al (2008). Because replicate tows were not made at each station, density of each sex was compared separately between years, sites, and depth strata by using single-factor analysis of variance (ANOVA), and P-values <0.05 were considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…The red deepsea crab (Chaceon quinquedens) ranges from the Gulf of Maine to the Gulf of Mexico, at depths from 200 to 1800 m, and temperatures of 5-8°C (Haefner and Musick, 1974;Wigley et al, 1975; Serchuk 1 ; Steimle et al, 2001;Wahle et al, 2008;NEFSC 2 ). Stocks along the Atlantic coast are considered a single population and distinct from the stock in the Gulf of Mexico.…”
mentioning
confidence: 99%
See 2 more Smart Citations